Analyzing Trio-Anthropometric Predictors of Hypertension: Determining the Susceptibility of Blood Pressure to Sexual Dimorphism in Body Stature - Ezemagu U. Kenneth; Uzomba Godwin Chinedu; Agbii Okechukwu Christian; P. O. Ezeonu; S. G. Obaje (International Journal of Hypertension)
Background. Several studies had suggested that complex body stature could be a risk factor of hypertension. Objectives. We aim to correlate body mass index (BMI), waist-hip ratio (WHR), and waist-height ratio (WHtR) of rural dwellers in Afikpo community, Ebonyi State, Nigeria, with blood pressure parameters. Furthermore, we aim to ascertain how each of the anthropometric variables affects blood pressure in men and women, respectively. Materials and Methods. A sample of 400 (200 males and 200 females) adults aged 18–89 years were selected for the correlation cross-sectional study. Data for weight, height, waist, and hip circumferences were collected by means of anthropometric measurement protocol with the aid of a calibrated flexible tape and health scale and mercury sphygmomanometer for measurement of blood pressure. A participant was classified as being hypertensive if systolic blood pressure (SBP) was >140 mmHg and diastolic blood pressure (DBP) >90 mmHg. Pulse pressure was recorded as the numeric difference of SBP and DBP. Results. The result revealed that male BMI and WHR were higher than those of females while female WHtR was higher than that of males (P < 0.01). The prevalence of hypertension failed to correlate with sex among participants in the study (χ2 = 0.567; P < 0.05). Variation in SBP and DBP of both sexes was dependent on BMI, WHtR, and waist and hip circumference, but not on WHR. The SBP of both sexes and female pulse pressure did correlate with age (P < 0.001). Waist circumference, BMI, and WHtR correctly predicted the variations in SBP, DBP, and pulse pressure. Conclusion. The strength of association of BMI, WHtR, and waist girth with SBP and DBP of both sexes was robust and similar, but inconsistent with WHR. Thus, a simple estimation of the trio-anthropometric predictors could serve as a means for routine check or preliminary diagnosis of a patient with hypertension.